222k views
2 votes
How do I solve this?

How do I solve this?-example-1

1 Answer

3 votes

Answer:

See below.

Explanation:


(5x^2y^3)^0/(-2x^(-3)y^5)^(-2)

First, note that everything to the zeroth power is 1. Thus:


=1/(-2x^(-3)y^5)^(-2)=(1)/((-2x^(-3)y^5)^(-2))

Distribute using Power of a Power property:


=(1)/((-2)^(-2)(x^(-3))^(-2)(y^5)^(-2)))

Make the exponents positive by putting them to the numerator:


=((-2)^2(x^(-3))^2(y^5)^2)/(1)


=(4x^(-6)y^(10))/(1)

Make the exponent positive by this time putting it to the denominator:


=(4y^(10))/(x^6)

User Satanicpuppy
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.